The Use of the Memrise Flashcard Application to Learn Adjectives by Class XI SAINS Students at SMA Negeri 2 Mataram - Izzatillah, M. Rizqy; Melani, Boniesta Zulandha; Udin; Tohir, Lalu (LITPAM, 2026)
Vocabulary mastery is an important component in English learning because it supports students' ability to understand and use language effectively. However, many students still struggle to master vocabulary, especially adjectives. Using technology-based learning media, such as the Memrise application, can be an alternative for improving students' vocabulary mastery. Therefore, this study aims to determine the effect of using the Memrise flashcard application on students' mastery of adjective vocabulary. This study used a quantitative approach with a pre-experimental design in the form of a one-group pre-test and post-test. The subjects were 35 students of grade XI SAINS 1 at SMA Negeri 2 Mataram in the 2025/2026 academic year. Data were collected through vocabulary tests administered before and after the treatment and analyzed using descriptive statistics and paired-samples t-tests in SPSS. The results showed that the students' average score increased from 80.03 in the pre-test to 92.66 in the post-test. The t-test results showed a p-value of 0.000 (p < 0.05), indicating a significant increase in students' mastery of adjective vocabulary after using the Memrise application. Based on these results, it can be concluded that the Memrise flashcard application is effective at improving students' mastery of English adjective vocabulary.